Upaya dan Kontribusi Indonesia dalam Proses Perdamaian di Afghanistan Melalui Bina-Damai - Robi Sugara (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2021)
This paper aims to explain the efforts and contributions made by the Government of Indonesia in assisting the peace process in Afghanistan. This study focuses on peacebuilding efforts undertaken by the Government of Indonesia for Afghanistan. This qualitative research with literature studies explains that the peace process in Afghanistan has been going on for a long time, as the conflict has occurred and has involved many parties. The peace process in Afghanistan involves the United Nations (UN), Afghanistan's neighboring countries, major countries, and other international communities including Indonesia. Indonesia's role in the Afghan peace process is not only by garnering support from the international community to continue to help peace in Afghanistan, but also primarily through peace-building through cooperation in the development and capacity building of the government and the people of Afghanistan. Indonesia's efforts to promote peace in Afghanistan also have the support of the international and domestic Afghan community. Peace-building efforts through various capacity building programs in several fields carried out by Indonesia are one of the important steps as a strategy to prevent conflict from returning and which are oriented towards sustainable and long-term peace building in post-conflict Afghanistan. This is Indonesia's contribution to helping create Afghanistan as a safe, democratic and prosperous country as well as for world peace.